Atomic scale insights into structure instability and decomposition pathway of methylammonium lead iodide perovskite. Issue 1 (December 2018) - Chen, Shulin; Zhang, Xiaowei; Zhao, Jinjin; Zhang, Ying; Kong, Guoli; Li, Qian; Li, Ning; Yu, Yue; Xu, Ningan; Zhang, Jingmin; Liu, Kaihui; Zhao, Qing; et al.
Abstract Organic–inorganic hybrid perovskites are promising candidates for the next-generation solar cells. Many efforts have been made to study their structures in the search for a better mechanistic understanding to guide the materials optimization. Here, we investigate the structure instability of the single-crystalline CH3 NH3 PbI3 (MAPbI3 ) film by using transmission electron microscopy. We find that MAPbI3 is very sensitive to the electron beam illumination and rapidly decomposes into the hexagonal PbI2 . We propose a decomposition pathway, initiated with the loss of iodine ions, resulting in eventual collapse of perovskite structure and its decomposition into PbI2 . These findings impose important question on the interpretation of experimental data based on electron diffraction and highlight the need to circumvent material decomposition in future electron microscopy studies. The structural evolution during decomposition process also sheds light on the structure instability of organic–inorganic hybrid perovskites in solar cell applications. Hybrid perovskites are highly promising for photovoltaic applications, but they are prone to decomposition. Here, the authors probe the stability of CH3 NH3 PbI3 films in a transmission electron microscope, defining the threshold conditions to avoid damage under the electron beam, and describing a decomposition pathway.